The Sonata Principle Reformulated for Haydn Post-1770 and a Typology of his Recapitulatory Strategies. Issue 1 (2015) - Riley, Matthew
Abstract: Haydn's 'recomposition' of the recapitulation is well known, but this article proposes, against received wisdom, that Haydn composed as though following a rule in the recapitulations of fast sonata-form movements from the 1770s onwards. The article extends William E. Caplin's functional theory to the Haydn recapitulation in order to revive the 'sonata principle', restated and limited to fast movements in Haydn's instrumental cycles. It then lays out a typology of Haydn's recapitulatory strategies that unfold within the constraints of the sonata principle.